2006
DOI: 10.1002/ijc.22468
|View full text |Cite
|
Sign up to set email alerts
|

Modulation by budesonide of DNA methylation and mRNA expression in mouse lung tumors

Abstract: Biomarkers are being developed that can aid in the evaluation of cancer therapeutic and chemopreventive drugs. Two suggested biomarkers found in mouse lung tumors are DNA hypomethylation and alterations in mRNA expression of genes, such as 18S RNA, caspase 3, cyclin B2, cyclin E1, iNOS and survivin. Budesonide is very efficacious in preventing lung tumors in mice, so that its ability to modulate biomarkers in lung tumors was determined. Lung tumors were induced by vinyl carbamate in female strain A/J mice. Bud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 15 publications
0
13
0
Order By: Relevance
“…In most cases the tumors were multiple, sometimes tending to confluence, while some adenomas and all carcinomas were large, invading a lobe or a whole lung. We refer to our previous papers (19, 33) for the microscopic appearance of the various histopathological types.…”
Section: Resultsmentioning
confidence: 99%
“…In most cases the tumors were multiple, sometimes tending to confluence, while some adenomas and all carcinomas were large, invading a lobe or a whole lung. We refer to our previous papers (19, 33) for the microscopic appearance of the various histopathological types.…”
Section: Resultsmentioning
confidence: 99%
“…The close correlation between 5-Lox and tumor inhibition observed in our study may indicate that the tumor inhibition effect of Licofelone was via 5-lipoxygenase pathway more than the cyclooxygenase pathway in our mouse lung tumor model. Previous studies by other investigators reported that gene (mRNA) expression of survivin decreased compared to that of untreated tumor control group by administering chemopreventive agents, budesonide (39) and targretin (40), in chemically-induced mouse lung tumor model. However, tumor inhibitory efficacy of Licofelone in our study has no mechanistic correlation with survivin expression as there was only a marginal inhibition of survivin (25%) at the highest dose of 0.3 mg/kg.…”
Section: Discussionmentioning
confidence: 99%
“…Budesonide is a potent anti‐inflammatory agent and is therefore expected to work also in advanced carcinogenesis stages, as it was previously demonstrated in A/J mice treated with B( a )P, in which this glucocorticoid inhibited all stages of tumor progression, from hyperplasia to cancer 32. Budesonide was also found to decrease the size of lung tumors, and reversed DNA hypomethylation and gene expression in lung tumors induced by vinyl carbamate in A/J mice 33. NAC has a variety of protective mechanisms in carcinogenesis, the primary one being its ability to scavenge reactive oxygen species (ROS) and other free radicals 21.…”
Section: Discussionmentioning
confidence: 69%